2022
DOI: 10.5888/pcd19.210258
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Uptake of Evidence-Based Interventions in 355 Clinics Partnering With the Colorectal Cancer Control Program, 2015–2018

Abstract: Purpose and Objectives Colorectal cancer screening rates remain suboptimal in the US. The Colorectal Cancer Control Program (CRCCP) of the Centers for Disease Control and Prevention (CDC) seeks to increase screening in health system clinics through implementation of evidence-based interventions (EBIs) and supporting activities (SAs). This program provided an opportunity to assess the uptake of EBIs and SAs in 355 clinics that participated from 2015 to 2018. Intervention Approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Whether champions served in leadership or other FQHC staff roles, their ongoing promotion of EBIs and SAs, and clear and consistent leadership support, was paramount to prioritize these efforts. CRC screening champions have been associated with increased CRC screening rates and higher overall clinic performance (DeGroff et al, 2018; Maxwell et al, 2020). Given the clear benefits of having a screening champion, awardees can prioritize working with clinics to develop concrete plans to establish, support, and maintain champions despite staff turnover or funding changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether champions served in leadership or other FQHC staff roles, their ongoing promotion of EBIs and SAs, and clear and consistent leadership support, was paramount to prioritize these efforts. CRC screening champions have been associated with increased CRC screening rates and higher overall clinic performance (DeGroff et al, 2018; Maxwell et al, 2020). Given the clear benefits of having a screening champion, awardees can prioritize working with clinics to develop concrete plans to establish, support, and maintain champions despite staff turnover or funding changes.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating EBIs and SAs into existing FQHC processes proved essential to CRCCP sustainability. Previous research identified an increase in the proportion of CRCCP partner clinics with sustainable EBIs and SAs in place over time, from 24 to 34 percentage points over a 2-year period (Maxwell et al, 2020). Understanding the extent to which EBI and SA implementation continues in CRCCP partner clinics following termination of CRCCP funding and TA could address long-term sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDC now requires all CRCCP awardees to partner with healthcare systems to implement EBIs; many of these partners are FQHCs serving populations experiencing health disparities and low screening rates. The CPCRN workgroup continues to partner with CDC to evaluate various aspects of CRCCP, such as implementation quality of mailed CRC fecal testing programs [ 45 ] and the uptake of EBIs and their association with change in CRC screening rates among participating primary care clinics [ 46 , 47 ]. Over time, the scope of the partnership has grown to include other types of capacity-building activities.…”
Section: Cpcrn Capacity-building Activitiesmentioning
confidence: 99%
“…Finally, the article by Maxwell et al ( 22 ) is a good example of the differences in uptake, implementation, integration, and sustainability of interventions proven effective in increasing colorectal cancer screening (CCS). The authors looked at implementation across 355 clinics partnering with the Colorectal Cancer Control Program and suggested that both technical and financial support, and the ability to integrate 6 of 8 strategies into electronic health records, may be key to implementation.…”
Section: Purpose Of the Special Collectionmentioning
confidence: 99%